2006
DOI: 10.1002/cncr.22089
|View full text |Cite
|
Sign up to set email alerts
|

Secondary chromosomal abnormalities predict outcome in pediatric and adult high‐stage Burkitt lymphoma

Abstract: Recent studies suggest that the hypodigms representing the two earliest Australopithecus (Au. anamensis and Au. afarensis) form an ancestor‐descendant lineage. Understanding the details of this possible transition is important comparative evidence for assessing the likelihood of other examples of ancestor‐descendant lineages within the hominin clade. To this end we have analyzed crown and cusp base areas of high resolution replicas of the mandibular molars of Au. anamensis (Allia Bay and Kanapoi sites) and tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 57 publications
6
52
1
Order By: Relevance
“…The most commonly deleted band was 13q34 (82%). The relationship between karyotypic abnormalities and outcomes showed that + 7q and del(13q) were independently associated with a significant inferior event free survival (EFS) (hazard ratio: 2·5 (P = 0·015) and 4·0 (P = 0·0003) respectively) (Poirel et al, 2009), which agrees with prior reports suggesting a worse outcome associated with 13q abnormalities (Fig 3B, C) (Lones et al, 2004;Onciu et al, 2006). Subsequently, Nelson et al (2009) utilized FISH to show a worse overall survival in patients with any 13q deletion (Fig 4).…”
Section: Cytogeneticssupporting
confidence: 88%
See 1 more Smart Citation
“…The most commonly deleted band was 13q34 (82%). The relationship between karyotypic abnormalities and outcomes showed that + 7q and del(13q) were independently associated with a significant inferior event free survival (EFS) (hazard ratio: 2·5 (P = 0·015) and 4·0 (P = 0·0003) respectively) (Poirel et al, 2009), which agrees with prior reports suggesting a worse outcome associated with 13q abnormalities (Fig 3B, C) (Lones et al, 2004;Onciu et al, 2006). Subsequently, Nelson et al (2009) utilized FISH to show a worse overall survival in patients with any 13q deletion (Fig 4).…”
Section: Cytogeneticssupporting
confidence: 88%
“…These translocations result in constitutive expression of the MYC gene driven by the immunoglobulin gene enhancer. Additional recurrent chromosomal abnormalities have been recognized with chromosomes 1, 6, 13, 17, and 22 most commonly involved (Lones et al, 2004;Onciu et al, 2006). A large cytogenetic study performed on an international trial in children and adolescents with mature B-cell lymphoma further characterized the secondary genetic changes detectable by karyotyping (Poirel et al, 2009).…”
Section: Cytogeneticsmentioning
confidence: 99%
“…Although a number of previous studies described genetic alterations in BL, [6][7][8][9][10][11][12][13] two recent major gene expression profiling studies 4,5 provided a molecular signature of BL that -at the same time -sharpened, but also broadened the diagnostic category of BL. Specifically, gene expression-defined BL appear to also include some aggressive B-cell lymphomas that do not fulfill the current strict WHO criteria 1 (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…4 In recent years, global genetic analyses including conventional karyotyping, comparative genomic hybridization (CGH) and array-based CGH have described secondary genomic alterations in BL. [6][7][8][9][10][11][12][13] One of the larger studies using CGH described gains of 12q, 22q, Xq and losses of 13q as the most frequent alterations in BL. 11 Moreover, abnormalities in 1q and 7q were associated with inferior outcome.…”
Section: Introductionmentioning
confidence: 99%
“…While the impact of additional cytogenetic abnormalities detected by conventional karyotype on clinical outcomes in Burkitt or Burkitt-like lymphomas has been the subject of several studies, [9][10][11] there is very little information regarding their diagnostic value in the classification of highgrade B-cell lymphomas. Although prompt diagnosis of Burkitt lymphoma and other high-grade B-cell lymphomas carrying MYC rearrangements is clinically important because they are aggressive and may require more intensive therapy, 12 the diagnosis sometimes can be challenging.…”
mentioning
confidence: 99%